Sustainable poultry development: Maintaining the role of indigenous chicken ecotypes while promoting high-yielding commercial chicken breeds - Birhanu, Mulugeta Y.; Dessie, Tadelle (CAB International, 2025)
Smallholder chicken production remains a fundamental part of household livelihood activities in developing countries. It has a range of contributions, including enhancing food and nutritional security, income generation, cultural and religious values, and environmental health. There is growing interest in improving the sub-sector’s production and productivity due to established evidence of its potential contribution to achieving multiple Sustainable Development Goals (SDGs), especially in the context of resource-poor households. Strategies that aim to enhance the sub-sector’s productivity may involve various approaches, including improving the productivity of indigenous chicken ecotypes and introducing high-yielding commercial chicken strains developed for the tropics. This case study presents a brief overview of the sub-sector’s potential contribution to achieving multiple SDGs and possible approaches that can be adopted by developing countries to achieve sustained development in the sub-sector. The case study highlights the need to simultaneously promote indigenous and commercial chicken-based production through context-specific policies and strategies.